Family Support and Degree of Injury are Determinants of Quality of Life in Patients with Ankle Injury: A Cross-Sectional Correlational Study - Laili Nur Rahma Novita Fitroh; Moh. Ubaidillah Faqih; Kusno Ferianto; Lukman Hakim (Jurnal Keperawatan Olahraga, 2026)
Background: Ankle injuries may lead to activity limitations and reduced quality of life. Family support and injury severity are believed to be related to quality of life in ankle injury patients, but empirical evidence in Indonesia remains limited. Aims:  This study investigated the relationship between injury severity, family support, and quality of life among patients with ankle injuries attending the Physiotherapy Clinic in Palang District. Methods: A cross-sectional correlational study was conducted with 101 patients selected through simple random sampling. Data were collected using the WHOQOL-BREF questionnaire, the Talar Tilt Test, and the Family Support Scale (FSS), and analyzed using Spearman’s Rho. Results:  The study found a significant positive relationship between family support and quality of life (p=0.000; r=0.647), indicating that higher family support is associated with better quality of life. A significant negative relationship was also found between the degree of injury and quality of life (p=0.000; r=0,511), indicating that more severe injuries are associated with lower quality of life; and 4). Conclusion:  Quality of life in patients with ankle injuries is significantly influenced by family support and injury severity; greater family support improves quality of life, while more severe injuries reduce it